A Framework For Garment Shopping Over The Internet - Jojic, Nebojsa; Rui, Yong; Zhuang, Yueting; Huang, Thomas S. (Handbook on Electronic Commerce, 1999)
In this chapter, we propose a framework for integrated design, advertisement and retailing of garments over the Internet. This on-line shopping framework would make use of the latest research in computer graphics, image processing, computer vision and artificial intelligence. We describe these technologies in more detail, and explain how they can be used to build a visually attractive and easy to use interface to an intelligent integrated system that fulfils most of the functions of the traditional production chain, while allowing for mass-customization.